Growth Factor Proteins and Treatment-Resistant Depression: A Place on the Path to Precision - Pisoni, Alice; Strawbridge, Rebecca; Hodsoll, John; Powell, Timothy R.; Breen, Gerome; Hatch, Stephani; Hotopf, Matthew; Young, Allan H.; Cleare, Anthony J. (Frontiers in Psychiatry, 2018)
Background: Since the neurotrophic hypothesis of depression was formulated, conflicting results have been reported regarding the role of growth factor proteins in depressed patients, including whether there are state or trait alterations found in patients compared to controls and whether they represent predictors of treatment response. Recently it has been hypothesised that heterogeneity of findings within this literature might be partly explained by participants’ history of treatment-resistant depression. This study aimed to investigate the role of growth factor proteins in patients with treatment-resistant depression (TRD) undergoing an inpatient intervention. Methods: Blood samples were collected from 36 patients with TRD and 36 matched controls. Patients were assessed both at admission and discharge from a specialist inpatient program. We examined biomarker differences between patients and non-depressed matched controls, longitudinal changes after inpatient treatment and relationship to clinical outcomes. Additionally, the influence of potential covariates on biomarker levels were assessed. Results: Patients displayed lower serum levels of brain-derived neurotrophic factor (OR = .025; 95% CI = .001, .500) and vascular endothelial growth factor-C (VEGFC; OR = .083, 95% CI = .008, .839) as well as higher angiopoietin-1 receptor (Tie2; OR = 2.651, 95% CI = 1.325, 5.303) compared to controls. Patients were stratified into responders (56%) and non-responders (44%). Lower VEGFD levels at admission predicted subsequent non-response (OR = 4.817, 95% CI = 1.247, 11.674). During treatment, non-responders showed a decrease in VEGF and VEGFC levels, while responders showed no significant changes. Conclusion: TRD patients demonstrate a deficit of peripheral growth factors and our results suggest that markers of the VEGF family might decline over time in chronically depressed patients in spite of multidisciplinary treatment. The action of angiogenic proteins may play an important role in the pathophysiology of TRD, and pending comprehensive investigation may provide important insights for the future of precision psychiatry.